Ecological and evolutionary dynamics of a model facultative pathogen: Agrobacterium and crown gall disease of plants. (4th December 2017) - Barton, Ian S.; Fuqua, Clay; Platt, Thomas G.
Summary: Many important pathogens maintain significant populations in highly disparate disease and non‐disease environments. The consequences of this environmental heterogeneity in shaping the ecological and evolutionary dynamics of these facultative pathogens are incompletely understood. Agrobacterium tumefaciens, the causative agent for crown gall disease of plants has proven a productive model for many aspects of interactions between pathogens and their hosts and with other microbes. In this review, we highlight how this past work provides valuable context for the use of this system to examine how heterogeneity and transitions between disease and non‐disease environments influence the ecology and evolution of facultative pathogens. We focus on several features common among facultative pathogens, such as the physiological remodelling required to colonize hosts from environmental reservoirs and the consequences of competition with host and non‐host associated microbiota. In addition, we discuss how the life history of facultative pathogens likely often results in ecological tradeoffs associated with performance in disease and non‐disease environments. These pathogens may therefore have different competitive dynamics in disease and non‐disease environments and are subject to shifting selective pressures that can result in pathoadaptation or the within‐host spread of avirulent phenotypes.